2011
DOI: 10.1002/jhm.945
|View full text |Cite
|
Sign up to set email alerts
|

Residents contributing to inpatient quality: Blending learning and improvement

Abstract: BACKGROUND:Quality improvement (QI) initiatives reduce medical errors and are an important aspect of resident physician training. Many institutions have limited funding and few QI experts, making it essential to develop effective programs that require only modest resources. We describe a resident‐led, hospitalist‐facilitated limited root cause analysis (RCA) QI program developed to meet training needs and institutional constraints.METHODS:We initiated a monthly quality improvement conference (QIC) at the Mount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…The ACGME has long emphasized the importance of developing skills in systems‐based practice and quality improvement to promote consistent excellent care. Harnessing this emphasis may be one strategy to support geriatrics curricula and translate knowledge into practice . A recent study demonstrated that specific educational interventions improved not only resident knowledge of the hazards of hospitalization in acutely ill older adults, but also their behavior, as reflected in their documentation, lending support to the thought that quality care for hospitalized elderly adults can be taught and outcomes potentially improved …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The ACGME has long emphasized the importance of developing skills in systems‐based practice and quality improvement to promote consistent excellent care. Harnessing this emphasis may be one strategy to support geriatrics curricula and translate knowledge into practice . A recent study demonstrated that specific educational interventions improved not only resident knowledge of the hazards of hospitalization in acutely ill older adults, but also their behavior, as reflected in their documentation, lending support to the thought that quality care for hospitalized elderly adults can be taught and outcomes potentially improved …”
Section: Discussionmentioning
confidence: 97%
“…Harnessing this emphasis may be one strategy to support geriatrics curricula and translate knowledge into practice. [13][14][15] A recent study demonstrated that specific educational interventions improved not only resident knowledge of the hazards of hospitalization in acutely ill older adults, but also their behavior, as reflected in their documentation, lending support to the thought that quality care for hospitalized elderly adults can be taught and outcomes potentially improved. 16 In addition to the need for resident education is the need for continued faculty training in the care of older adults.…”
Section: Discussionmentioning
confidence: 99%
“…A few promising studies have led to persistent organizational changes (Kirkpatrick Level 4) . Examples of such organizational changes are the frequency of red‐flag symptoms identified in back pain presentations in a general practice, all patient receiving a physical examination within 6 hours of admission to a mental health unit, and implementation and use of central line kits and team and completion of discharge summaries before discharge from the institution.…”
Section: Curricular Outcomesmentioning
confidence: 99%
“…Nevertheless, conducting and reporting root cause analyses is now a common requirement of accredited medical institutions [4]. More recently, the benefit of implementing quality improvement methodology and skills, including root cause analysis, has in many places become the de rigueur for residents and students, as junior ranks of the medical profession [8–10].…”
Section: Introductionmentioning
confidence: 99%